2022
DOI: 10.3389/fonc.2022.852365
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel necroptosis-related classifier to predict prognosis and guide immunotherapy in breast invasive carcinoma

Abstract: BackgroundNecroptosis plays a crucial function in the progression of breast invasive carcinoma (BRCA). It may be triggered in cancer therapy to enhance anti-tumor immunity. However, the functions of necroptosis in tumors and its relationship with the tumor microenvironment (TME) remain largely unclear.MethodsNecroptosis-related genes (NRGs) were collated from high-quality literature reviews. A robust risk model was constructed to systematically evaluate the clinical value, functional status, effects exerted by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…12 While there are limited studies of the antitumor potential of inciting necroptosis in immune-compromised and immune-intact ovarian cancer models, multiple studies reveal that necroptosis-related gene signatures predict improved responses to immune therapy. [13][14][15] In this work, evaluation of VDX-111 in both a patient-derived xenograft and a syngeneic ovarian cancer murine model demonstrated survival benefit and antitumoral effects. While both necroptosis and apoptosis effectors were changed in response to drug treatment, we focused on necroptosis-related cell death due to its consistent induction across all models and its limited understanding in ovarian cancer.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…12 While there are limited studies of the antitumor potential of inciting necroptosis in immune-compromised and immune-intact ovarian cancer models, multiple studies reveal that necroptosis-related gene signatures predict improved responses to immune therapy. [13][14][15] In this work, evaluation of VDX-111 in both a patient-derived xenograft and a syngeneic ovarian cancer murine model demonstrated survival benefit and antitumoral effects. While both necroptosis and apoptosis effectors were changed in response to drug treatment, we focused on necroptosis-related cell death due to its consistent induction across all models and its limited understanding in ovarian cancer.…”
Section: Introductionmentioning
confidence: 84%
“…Necroptosis is mediated in a caspase‐independent fashion through Receptor Interacting Protein Kinases (RIPK1/3) and Mixed Lineage Kinase domain‐like (MLKL) and leads to a robust inflammatory response and immune activation 12 . While there are limited studies of the antitumor potential of inciting necroptosis in immune‐compromised and immune‐intact ovarian cancer models, multiple studies reveal that necroptosis‐related gene signatures predict improved responses to immune therapy 13–15 …”
Section: Introductionmentioning
confidence: 99%
“…In the majority of cases, BIRC3 is regarded as an oncogene with antiapoptotic functions; however, in BC, BIRC3 does not regulate any pathway of apoptosis ( 32 ). A recent study by Zhou et al ( 33 ) showed that BIRC3 was highly expressed in BC, and its high expression was associated with favorable prognosis. The dual function of BIRC3 may depend on the type of cancer and/or the molecular subtype of BC.…”
Section: Discussionmentioning
confidence: 99%
“…MRPL14 is part of 2 intersubunit bridges in the assembled ribosome, which might be involved in the occurrence and development of thyroid tumors ( 72 ). RFK is essential for TNF-induced ROS production, which can influence the progress of breast invasive carcinoma and human prostate cancer ( 71 , 73 ). However, the role of COQ4, MCRIP2, MRPL50, MRPL14, RFK, and NMNAT3 in pancreatic tumor has not been reported.…”
Section: Discussionmentioning
confidence: 99%